Pengaruh Model Problem Based Learning (Pbl) Berbantuan Media Powerpoint Dan Media Realia Terhadap Keterampilan Berpikir Kritis Siswa Pada Materi Ipa Di Kelas V Sekolah Dasar - Arna Juwairiyah (Jurnal Sultra Elementary School, 2022)
This study aims to determine the improvement of students’ critical thinking skills in science learning using the Problem-Based Learning (PBL) model assisted by PowerPoint media and realia media. This research employed a quasi-experimental design. The findings revealed that there was a significant effect on students’ critical thinking skills when taught using the PBL model assisted by PowerPoint and realia media. The average N-Gain score of students’ critical thinking skills in the class that used the PBL model assisted by PowerPoint media was significantly higher (0.58) compared to the class that used the PBL model assisted by realia media (0.48). This indicates that the use of the PBL model with PowerPoint media is more effective in improving students’ critical thinking skills in science learning than the PBL model with realia media.